The Impact of the International Livestock Research Institute - McIntire, John; Grace, Delia (CABI, 2021)
This book contains 18 chapters that describes the evolving and multi-faceted roles of ILRI in addressing these and other global challenges in nearly a half century of research. ILRI researchers and partners took leading roles, for example, in the following. This volume can serve as a reference and resource for all interested in the role of livestock in agricultural transformation and sustainable development. It should be useful for distilling, learning from, and building on past work and lessons hopefully to inform and inspire students, researchers and research managers and their investors.